Revascularization limb salvage in chronic limb-threatening ischemia: does open surgery still the best option in the era of endovascular therapy? - Ashabul Anhar; Yopie Afriandi Habibie (Intisari Sains Medis, 2020)
Introduction: Chronic limb-threatening ischemia (CLTI) is considered the most severe pattern of peripheral artery disease. It is defined by the presence of chronic ischemic rest pain, ulceration or gangrene attributable to the occlusion of peripheral arterial vessels who suffered from diabetes mellitus type 2, and also associated with physical, as well as psychosocial, consequences such as amputation and depression. Successful revascularization decreases the major amputation rate in patients with CLTI. The efficacy of peripheral bypass grafts and percutaneous transluminal angioplasty in accomplishing limb salvage has been recognized.Case Description: A 42-year-old man came to the RSUZA emergency room with chief complaints claudication above the right thigh and continuous pain (rest pain) at the right lower extremity since 9 months ago. History of finger amputation 2nd, 3rd and 4th right foot since 10 months ago at local hospital, and now there are necrotic wounds on his toes. Patients suffered from type 2 diabetes mellitus and have bad habits such as smoking 3 packs a day all the time. Physical examination has a wound in the lower leg area of more than 10 cm x 8 cm. Right ankle-brachial index (ABI) 0.6 and left ABI 1.3. CT-angiography (CTA) shows infra inguinal type D TASC II classification. A revascularization procedure is performed to salvage the limb with the right femoro-popliteal bypass technique with graft R-SVG and debridement in the right lower leg area so that chronic right lower limb ischemia can be overcome. Systemic heparinization was given post operatively and complaints of pain in the right lower limb begin to disappear. Patient was discharged on the 5th day of treatment with good results.Conclusion: Open surgical bypass continues to be a primary treatment of choice, durable approach in a significant proportion of patients. Lower extremity bypass grafting is most successful with a good quality, long, single-segment autogenous vein of at least 3.5mm diameter.Â